Characterizing historical textiles and clothing with proteomics - Solazzo, Caroline (2019)
This paper is a review of proteomics and mass spectrometric techniques used for the study of historical textiles and garments. First applied on archaeological animal fibers over a decade ago, proteomics has made important contributions to the analysis of ancient proteins and to cultural heritage studies. The field of proteomics has the potential to give a better understanding of the modes of fabrication of ancient textiles, their composition and pathways of degradation, as well as the development of animal fibers through domestication and breeding. This review summarizes current analytical methods, describes the different sources of animal fibers and their biomolecular characteristics and methods of analysis, and finally presents the main applications of proteomics to historical clothing.   Received: 2018-7-5 Revised: 2018-11-14 Accepted: 2018-12-11 Online: 2019-2-14 Publication: 2019-4-30